Sentidos e significados que professores atuando em escolas de periferia constituem para as dificuldades e desafios encontrados em sua profissão - Vieira, Elisandra Felix (2013)
This study aimed to grasp the senses and meanings that outlying public school teachers constitute for the difficulties and challenges they faced in their profession as well as how, according to them, these problems affect their ways of thinking, feeling and acting. Nowadays, teachers work is affected by proletarization, precarization and intensification of work, since they act in organizations with low budgets, doing a variety of functions that are not directly related to their profession, with rare opportunities of continuing professional development and, moreover, having to double or triple their daily schedule in order to make a paltry salary. Given this situation, we found it necessary to understand how these hardships affect teaching, more specifically that of Cristina, a teacher within the public school network of the municipality of São Paulo, in a Unified Educational Centre (CEU). From her narrative, as well as those of six other educators, it was possible to identify different indicators of subjective senses in these educational situations. Through articulation of the speeches, significations were identified that were gleaned as part of a dialectically determined society by means of social mediation, forming a picture that is, as the actual literature frequently points out, probably shared by the teaching professionals. The data obtained was analyzed according to the procedure suggested by Aguiar e Ozella (2006, 2013) and named Nuclei of Significations. In light of theoretical and analytical assumptions of sociocultural psychology and its main categories of analysis (historicity, mediation, thought, speech, senses and meanings), the results revealed that the distance between what is expected of the teachers and the little that they are offered in terms of resources and training has created feelings of abandonment and the desire to abscond from their professional responsibilities, as well as indifference and depersonalization, resulting from institutional problems which oppress them, producing an incapability to theorize beyond what they experienced and to understand the historical, political and economic determinations that impoverish the teaching career. Restricted by a precarious initial and continuous professional formation and by the limits of time and economic resources, the teachers need to be satisfied to teach at a level that is hardly related to pedagogical scientific knowledge